In situ fabrication of Co0.85Se and Ni0.85Se hierarchical thin films as high-performance counter electrode for dye-sensitized solar cells. (1st November 2016) - Yao, Yueh-Yun; Chao, Hsi-Jung; Chou, Tzung-Han; Chang, Sheng Hsiung; Wu, Chun-Guey; Ling, Yong-Chien; Chang, Jia-Yaw
Graphical abstract: Co0.85 Se and Ni0.85 Se hierarchical thin films assembled using nanosheets and nanoparticles are deposited in situ on an FTO substrate for an efficient counter electrode in dye-sensitized solar cells. Highlights: The hierarchical structures were grown in situ on FTO by a microwave-assisted method. The hierarchical structures were consisting of nanoparticles and nanosheets. The hierarchical structures were used as counter electrode without post-treatment. Co0.85 Se and Ni0.85 Se showed good catalytic activity for electrolyte regeneration. The DSSC with the Co0.85 Se showed a highest conversion efficiency of 8.58%. Abstract: Cobalt selenide (Co0.85 Se) and nickel selenide (Ni0.85 Se) hierarchical thin films assembled using by nanosheets and nanoparticles, respectively, were fabricated in situ on fluorine-doped tin oxide substrates in a ligand-free environment to prepare counter electrodes (CEs) for dye-sensitized solar cells (DSSCs) consisting of a N719-sensitized nanocrystalline TiO2 film. The Co0.85 Se- and Ni0 .85 Se-based CEs were rapidly synthesized via a microwave-assisted one-step method at 170 °C within a short reaction time of 10 min. The morphology and structure of the Co0.85 Se and Ni0.85 Se hierarchical thin films were characterized by means of scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. The results of electrochemical impedance spectroscopy, cyclic voltammetry, and Tafel polarization measurements showed that both CEs exhibited good electrocatalytic activity and I − /I3 − redox reactions and much lower charge-transfer resistance. A power conversion efficiency (PCE) of 8.58% for the Co0.85 Se CE-based solar cell was obtained, which is comparable to that of cells using Pt CEs (8.57%); 7.09% PCE was obtained for the Ni0.85 Se-based CE. The results suggest that in situ-prepared Co0.85 Se-based CEs could be a promising alternative to Pt-based CEs for DSSCs.